ANALISIS PASAL 1338 AYAT (3) KUH PERDATA DALAM KONTRAK JASA INDUSTRI MIGAS - Budiarti, Wijaya; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Abstract: In the context of data privacy law, a valid contract is an element that exists in every agreement, whether it be between a private citizen and the government or between a private citizen and a corporation. The thing meant by good faith in this case is a person or individual who uses good faith. Good economic theory states that a person should not take advantage of other parties to advance his own interests or take advantage of other people. As a result, a contract or other legal agreement does not just have to be based on language that the parties involved agree upon instead, the court can also intervene to resolve disputes by establishing a contract outside of legal language that is based on sound legal principles. The purpose of the paper is to analyze the above-mentioned subheadings as a means of analyzing the principles of good itikad in the execution of contracts and agreements, as well as to provide examples of what exactly needs to be included in the commitment and good itikad of both parties, particularly in the fields of mining and the gas industry.Keywords: Itikad Baik, Pasal 1338, KUHP, Hukum Perdata, Industri.